On the microstructure of TiHfOx thin films - Domaradzki, Jarosław; Borkowska, Agnieszka; Kaczmarek, Danuta; Prociów, Eugeniusz L.; Wasilewski, Radosław; Ciszewski, Antoni (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Transition metal oxides, whose optical band gap might be modified by doping or manufacturing using two (or more) oxides with different band gaps, are good candidates for host matrices in luminescent devices. This paper presents structural properties of TiHfOx thin films and analysis of dependence of their optical properties on thin film structure. In order to examine the microstructure of manufactured thin films the X-ray diffraction (XRD) and atomic force microscopy (AFM) were applied. The optical properties of manufactured thin films were investigated by optical transmission method in the spectral range from 200 to 1400 nm.
Optica Applicata, Vol. 35, 2005, nr 3, s. 431-435
Keywords: optyka; multicomponent oxide; thin film; magnetron sputtering; hot target